2018
DOI: 10.1111/bjd.17025
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal water loss in healthy adults: a systematic review and meta-analysis update

Abstract: Reference estimates are useful for clinical study planning and interpretation of results. TEWL is highly dependent on skin area, and our results further support the symmetry between right and left measuring sites. TEWL in elderly people seems to be generally similar or decreased compared with younger individuals, but available evidence is limited. Reporting of TEWL should be improved: mean and spread parameters should always be reported in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
146
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(176 citation statements)
references
References 50 publications
(99 reference statements)
6
146
2
3
Order By: Relevance
“…In the present study, different body sites were used, however, compared to the corresponding skin site of every individual. This measurement approach was supported in a recent systematic review and meta‐analysis, which found a symmetrical pattern of TEWL values on the right and left sides of the body of each individual …”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In the present study, different body sites were used, however, compared to the corresponding skin site of every individual. This measurement approach was supported in a recent systematic review and meta‐analysis, which found a symmetrical pattern of TEWL values on the right and left sides of the body of each individual …”
Section: Discussionmentioning
confidence: 77%
“…Though TEWL is insufficient to quantify the intrinsic skin barrier function alone, it is a standardized and recognized direct, noninvasive overall measurement in the evaluation of the skin barrier function . The validity of TEWL measurements is highly dependent on standardized conditions, including room temperature, relative humidity, and particularly the anatomical site being measured . In the present study, different body sites were used, however, compared to the corresponding skin site of every individual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biophysical parameters are strongly influenced by intrinsic and extrinsic factors like age, sex, race, circadian rhythm, season, exercise and acclimatization period; 22,95,99,100,[124][125][126][127][128][129][130][131] therefore data collection is inherently difficult to standardize.…”
Section: Discussionmentioning
confidence: 99%